Influence of herbicides under biofertilizer application on fennel (Foeniculum vulgare) yield and quality with special reference to herbicide residues - Abdallah, Ibrahim (2023)
The results indicated that under all rates of the biofertilizers, the two herbicides applied individually caused significant reduction in growth parameters of the fennel plant estimated. Hand weeding (untreated check) increased fruit yield by 63% and oil yield by 78% compared to unweeded control, while sequential application of pendimethalin + fluazifop increased fruit yield by 45% and oil yield by 83% under biofertilizers at the rate of 2:1:1. Slight decrease in protein content using pendimethalin + fluazifop (12.94, and 12.96%) compared to 13.56% for hand weeding was observed. However, fluazifop alone showed no significant differences (13.63 and 13.13%) during both seasons under the biofertilizer rate of 2:1:1. No detectable residues of pendimethalin and fluazifop applied alone or sequentially were found in the analyzed dry seeds.